E4An Ultrastructural Study by Transmission Electron Microscope of Exocrine Pancreatic Cells in Diabetic Rats Treated with Herbal Combination (Baghdad Science Journal, 2019)
The current study was designed to investigate the alterations in the ultrastructure of orgenelles and cellular activity of exocrine pancreatic acini of experimentally induced-diabetic rats and to assess the usefulness of herbal combination supplementation in improving the ultrastructure and cellular activity of exocrine pancreas. The number of albino male rats used were 24 which divided into equally 4 groups; group I: control group, group II: alloxan-induced diabetes mellitus (single intraperitoneal dose of alloxan 120 mg/kg for 3 days), group III: herbal combination treatment composed from the extracts of fenugreek seeds (Trigonella foenum-graecum), black cumin (Nigella sativa) seeds, rhizomes of ginger (Zingiber officinale), leaves of olive (Olea europeae), and seeds of ash (Fraxinus ssp). Each rat given 2.5 ml (0.5 ml from each five mixed plant extracts used) for 2 months. group IV: diabetes was induced as group II and treated with herbal combination as group III for 2 months. The processing for investigating by transmission electron microscopy were carried out for all pancreata taken from all groups. There was significant reduction (p<0.05) in mean of FBG levels in diabetic rats treated with herbal combination (group IV) as compared to diabetic control and could revert FBG to normal value compared to negative control The results of examination of semithin and ultrathin sections in diabetic rats revealed many degenerative changes in the exocrine pancreatic tissue in comparison to control group. These degenerative changes can be summarized as disturbances in the arrangement of pancreatic acinar cells and decreased secretory granules in addition to the vacuolation of cytoplasm and pyknotic nuclei were observed in semithin sections. Moreover, degenerated nuclei, vacuolation of cytoplasm, fragmentation of rough endoplasm reticulum and degranulation of the most pancreatic acinar cells were noticed in ultrathin sections. In contrast, the acinar cells of group administrated with herbal combination only had normal ultrastructure, cellular activity, and nuclei, well-developed rough endoplasmic reticulum with abundant zymogen granules. Also, most of the acinar cells retrieved their normal ultrastructure and cellular activity in diabetic group treated with herbal combination and herbal combination could decrease most of the degenerative changes caused by alloxan-induced diabetes. In conclusion, the daily supplementation with this herbal combination to diabetic rat for 2 months could achieving promising effects due to its cytoprotective influence and showed the ability to decreased degenerative damage in the ultrastructure and cellular activity of exocrine pancreatic acini in type 2 diabetic rats.